Modifying an artificial diet for mass rearing mediterranean fruit fly, Ceratitis capitata (Diptera: Tephritidae), using locally available maize meal - Rini, Lulama Angela (Stellenbosch : Stellenbosch University, 2012)
Thesis (MSc)--University of Stellenbosch, 2003.